1964
DOI: 10.1680/geot.1964.14.3.262
|View full text |Cite
|
Sign up to set email alerts
|

The Moisture Characteristics, Composition and Structural Analysis of a Red Clay Soil from Nyeri, Kenya

Abstract: Synopsis Laboratory studies have shown that a red clay soil from Nyeri, Kenya, (which occurred immediately beneath the top soil and was seasonally air dried in situ) possessed unusual properties, including an excessively high moisture sorption, increase in index values with prolonged mixing and abnormally low optimum dry density for B.S. compaction. The explanation of these properties is shown in this Paper to lie in the mineralogy and structure of the soil, and by use of colour studies it is shown that the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1972
1972
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…However, significant positive correlations were found between PL and silt content, and significant negative correlations were obtained between LL, PL and SL and sand content (Table 3). When the relations between soil consistency limits and clay content are weak, the effect might be attributed to fractions coarser than the clay fraction or to the existence of aggregated clay-sized particles (Coleman et al, 1964;Campbell, 2001). However, Odell et al (1960), de Jong et al (1990 and Keller & Dexter (2012) found strong positive correlations between clay content and Atterberg limits.…”
Section: Descriptive Statistics and Correlation Analysis Resultsmentioning
confidence: 99%
“…However, significant positive correlations were found between PL and silt content, and significant negative correlations were obtained between LL, PL and SL and sand content (Table 3). When the relations between soil consistency limits and clay content are weak, the effect might be attributed to fractions coarser than the clay fraction or to the existence of aggregated clay-sized particles (Coleman et al, 1964;Campbell, 2001). However, Odell et al (1960), de Jong et al (1990 and Keller & Dexter (2012) found strong positive correlations between clay content and Atterberg limits.…”
Section: Descriptive Statistics and Correlation Analysis Resultsmentioning
confidence: 99%
“…Coleman et al [42] reported maximum dry density for the Nyeri region in Kenya at around 1313.6 kg/m3, and the optimum moisture content was 36% which is correspondingly high. However, the value reported for red clay was low compared with average clay soils.…”
Section: Compaction Testmentioning
confidence: 99%